The Effect of Interest Rates, Inflation, and Money Supply on Economic Growth through Exchange Rate Transmission in Indonesia - Anugrah Tri Saputra; Sri Astuty; Irwandi; Regina; Citra Ayni Kamaruddin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Understanding monetary transmission mechanisms is critical for emerging open economies navigating external volatility. This study investigates the direct and indirect impacts of interest rates, inflation, and money supply on Indonesia's economic growth from 2014 to 2024, examining the mediating role of the Rupiah-to-USD exchange rate. Utilizing a quantitative explanatory design with annual time-series data from Bank Indonesia and BPS, the research applies Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Empirical results demonstrate a high coefficient of determination for the exchange rate (R² = 0.939) and economic growth (R² = 0.359). Findings reveal that interest rates exert a significant direct effect on growth (coef = 0.417, p = 0.003) but have an insignificant impact on the exchange rate. Inflation positively influences growth (coef = 0.650, p = 0.001) while negatively affecting the exchange rate (coef = -0.313, p = 0.007). The money supply significantly impacts both exchange rates (coef = 0.791, p = 0.000) and economic growth (coef = -0.390, p = 0.025). Crucially, the exchange rate acts as a potent mediating channel (coef = 0.894, p = 0.000), transmitting shocks to real output. The findings underscore that monetary policy must integrate exchange rate stability and liquidity management alongside interest rate adjustments.